Law Enforcement For the Creators of Pornographic Content on the OnlyFans Platform (Universitas Terbuka, 2025)
Based on Indonesian law, the production of pornographic content based on the onlyfans site is a crime regulated in the Criminal Code and Law Number 44 of 2008 concerning Pornography regarding crimes related to pornography. Cases of pornographic content that are carried out often occur in Indonesia. Specifically for pornographic content based on onlyfans sites, there are only Siskae and Dea Onlyfans. For the production of pornographic content on Onlyfans, the perpetrator's actions can be subject to criminal sanctions because they fulfill the elements in the Criminal Code, the ITE Law, the Trade Law, and the Pornography Law. The research method used in this study is a doctrinal research method with primary, secondary and tertiary legal sources. The purpose of this research is to identify and analyze criminal law arrangements for creators of pornographic content based on the onlyfans site on social media, and law enforcement for creators of pornographic content based on the onlyfans site on social media. The results of this study, the researchers concluded that in addition to the Formulation of Criminal Acts for creators of pornographic content based on the onlyfans site, Article 4 paragraph (1) letters d and e of Law Number 44 of 2008 concerning Pornography can properly, clearly and firmly ensnare content creators. Second, existing law enforcement against pornographic content creators in Indonesia has not been carried out evenly. The ongoing legal process also has significant differences. Researchers are of the view that in law enforcement it is necessary to use the theory of legal certainty to provide equality in the law enforcement process for all existing pornographic content creators.